Mengenal Lebih Dekat Perbedaan BPJS Ketenagakerjaan Dan BPJS Kesehatan - Efitra, Efitra; Rozanah, Rozanah; Ardiansyah Lubis, Kurnia; Ahmad Sirojudin, Said; Mukmin, Amirul (Jurnal Syntax Fusion, 2023)
The government has a social security program through the Employment and Health Social Security Administration Agency (BPJS). However, there are still many Indonesians who find it difficult to distinguish between BPJS Employment and BPJS Health. In fact, often the two are considered are same because they have similar names, namely based on BPJS. The government has made it mandatory for people who work, both in the formal and informal sectors, to have BPJS. Including those who have just entered the world of work, are required to have BPJS Employment and BPJS Health.